Arthroscopy - Suarez-Ahedo, Carlos (IntechOpen, 2022)
This book covers a physical examination, imaging, differential diagnoses, and treatment of articular pathologies. For each diagnosis, the book sets out the typical presentation, options for non-operative and operative management, and expected outcomes. Practical and user-friendly, Arthroscopy is a useful resource for medical students and practitioners seeking fast facts on diagnosis and management. Its format makes it a perfect quick reference and its content breadth covers commonly encountered orthopedic problems in practice.